Sistem Pemilihan Smartphone Berdasarkan Spesifikasinya Pada Mahasiswa Sistem Informasi Universitas Tanjungpura Menggunakan Metode Simple Additive Weighting (SAW) - Renny Puspita Sari; Bayu Saputra (Universitas Budi Darma, 2021)
Current technology is often used by all groups, one of which is students in the Information Systems department at Tanjungpura University. One of the technologies used is a Smartphone which is a tool for students to communicate with each other even during the current pandemic, Smartphones are used for learning as well and each Smartphone has its own specifications that make it superior to other Smartphones, of course with the number of Smartphones circulating in the market. will be confused in making the selection, thus the decision support system to choose a Smartphone based on the specifications is made for the purpose of assisting in the selection of the Smartphone. The Simple Additive Weighting (SAW) method is used to complete the decision support system for Smartphone Selection During the Pandemic for the Tanjungpura University Student Information System which uses weighted summation for each performance rating for each alternative. In this study, the results of the calculations obtained from the survey are Samsung S21 5G with a value of 73.75, Iphone 11 64GB with a value of 48.75, Vivo Y17 with a value of 81.25, Asus ROG Phone 5 with a value of 80, Oppo A92 and with a value. 96.